Proteksi Arus Netral dan Suhu Transformator Berbasis IoT Dampak Beban Tidak Seimbang - Pratama, Rafiif Ariesandi Rola; Indhana Sudiharto; Suhariningsih (Elposys: Jurnal Sistem Kelistrikan, 2025)
Current imbalance results in neutral current and an increase in the temperature of the distribution transformer body. Due to the large number and scattered locations, maintenance of the transformers is carried out at least three times a year. Therefore, the authors developed a laboratory-scale device, which is a miniature neutral current and temperature increase protection system based on the Internet of Things (IoT). The results from the laboratory-scale testing of this protection system will disconnect the load when the current imbalance reaches ≥25% and the body temperature reaches ≥90˚C. Notifications will be sent to Telegram if the load current imbalance is in the range of 10%-14% (sufficient), 15%-24% (insufficient), and ≥25% (poor), and temperatures of 83-84℃ (sufficient), 85-89℃ (insufficient), and ≥90℃ (poor). The miniature protection can disconnect the load when the imbalance value is 25.92% and the temperature reaches 90˚C. Monitoring data is stored in a logger and can be downloaded. Thus, this tool can enhance reliability and help PLN personnel work more effectively.